VD_FINDINFO Décision / 2021 / 546 vom 23. April 2021 - VD Tribunal cantonal (2021)
NON-LIEU, USUREDROIT PÉNAL, CONTRAINTEDROIT PÉNAL | 157 ch. 1 CP, 180 al. 1 CP, 319 al. 1 CPP (CH), 429 al. 1 let. a CPP (CH), 430 al. 1 let. a CPP (CH)